Optimizing Performance through Organizational Culture and Work Spirituality: Empirical Study of Lecturer Performance in Private Institutions of Higher Education in Indonesia - Dien, Yudhi; Joeliaty,; Hilmiana,; Yunizar, (International Journal of Psychosocial Rehabilitation, 2020)
Performance is a topic in the field of human resource management that persistently becomes a main issue. Quality performance is the final result expected by every organization. This study aims to generate a model of performance optimization with servant leadership through organizational behavior and work spirituality. The subjects of this study were 147 private university lecturers in Indonesia. Quantitative methods were employed in this study using exploratory factor analysis (CFA) and SEM by using Lisrel 8.8 software. The results of this study indicate that sevant leadership has no direct effect on lecturer performance. However, servant leadership has a significant effect indirectly on the performance of lecturers through organizational culture and work spirituality. The results of this study can be used as a practical guide to improve the performance of lecturers in the organization.